The Effect of Magnesium Sulfate on Contraction of Pregnant Women with Cases of Partus Premature Imminent in District General Hospitals Mentawai Islands - Rozyka, Fafelia; Permata, Silvie; Yona, Thins; Herayono, Febby (PT. Riset Press International, 2024)
In 2020, it was recorded that the number of neonatal deaths in West Sumatra was 104, with 18 cases being the cause of prematurity, where the Mentawai Islands district had the highest ranking of neonate deaths with 44 deaths and 10 cases being the cause of prematurity. This research aims to determine the effect of administering magnesium sulfate therapy on contractions of pregnant women in cases of imminent premature labour at the Mentawai Islands District Hospital in 2021. This type of research is pre-experimental with a Grup Pretest-Post Test design because in this study a random sample was not carried out by taking samples from secondary data retrospectively. Data taken came from medical records of inpatients who had a diagnosis of premature labour (ICD Total sampling was taken with a total sample size of 48, and statistical data analysis using the McNemar test. Data from 48 research subjects experienced contractions and received magnesium sulfate therapy. During monitoring after administering magnesium sulfate, 3 subjects still experienced contractions and 45 subjects did not experience contractions. Uterine contractions occurred significantly more before magnesium sulfate therapy than after magnesium sulfate therapy (P<0.005). There is a significant relationship between administering magnesium sulfate to patients with preterm labour to stop uterine contractions at the Mentawai Islands District Hospital. Apart from being a tocolytic therapy, magnesium sulfate also has a neuroprotectant effect so it is highly recommended for therapy in cases of premature parturition.